INTEGRATIVE OMICS APPROACHES IN UNRAVELING PLANT STRESS MECHANISMS - Sikarwar, Ragini (International Journal of Research -GRANTHAALAYAH, 2025)
Plants encounter a wide array of abiotic and biotic stresses, including drought, salinity, extreme temperatures, pathogens, and heavy metals, which severely limit agricultural productivity. Understanding stress responses at the molecular level is crucial for developing resilient crops. In recent years, omics technologies—genomics, transcriptomics, proteomics, metabolomics, and phenomics— have emerged as powerful tools for dissecting the complex regulatory networks governing plant stress adaptation. This article reviews advances in integrative omics approaches that provide holistic insights into plant stress tolerance mechanisms. Genomics has facilitated the identification of stress-responsive genes, while transcriptomics reveals dynamic gene expression under stress. Proteomics and metabolomics provide information on protein modifications and metabolic fluxes, respectively, and phenomics bridges molecular data with physiological responses. Integrating multi-omics datasets with computational modeling and systems biology enables the construction of predictive networks for stress resilience. Case studies on Arabidopsis thaliana, rice (Oryza sativa), wheat (Triticum aestivum), and soybean (Glycine max) demonstrate the power of omics integration in identifying biomarkers, regulatory hubs, and candidate genes for crop improvement. Challenges remain in data standardization, big data analysis, and translating omics insights into field applications. Nevertheless, integrative omics promises a transformative path toward sustainable agriculture in the era of climate change.